Kelayakan Teknis dan Finansial Penerapan Inovasi Teknologi Jajar Legowo Super pada Sentra Produksi Padi Sawah Irigasi di Wilayah Sumatera - Priatmojo, Bhakti; Wardana, I Putu; Adnyana, Made Oka (Jurnal Penelitian Pertanian Tanaman Pangan, 2019)
Jajar Legowo Technology Super (Jarwo Super, JS) is an integrated rice cultivation technology on irrigated rice field based on jajar legowo 2:1 to improve rice yield by utilizing the influence of the border effect. Jajar legowo 2: 1 is difined as crops placement technique that every two rows of rice plants followed by one blank row and repeted for next rows). Part of the Jajar Legowo Super Technology component are: 1) New Superior Varieties (VUB); 2) bio-decomposer; 3) bio-fertilizers; 4) bio-pesticides and innorganic pesticides; and 5) agricultural equipment and machinery. The purpose of this study was to determine the technical feasibility, financial feasibility, and sensitivity performance of jarwo super technology (JS) rice farming at the farmer level compared to farmers who applied conventional rice cultivation or non-jarwo (NJS) technology. The research was carried out in three provencies in Sumatera such as: Aceh Province, North Sumatra and South Sumatra Province. Increased rice productivity in Aceh province is 31%, South Sumatra 37% and North Sumatra 12%. JS financial analysis of total revenue, allocation of JS cultivation cost is about 37.19% and NJS farmer 43.59%, with R/C ratio 2,69 for JS farmers, while for NJS R/C 2,29. Meanwhile, B/C ratio 1,69 for JS farmers and 1.29 for NJS farmers. The value of MBCR of introduced super jarwo technology is 5,25 which means the introduction of super jarwo technology is worth pursuing because withÂ  addition production costs of Rp 1 million can increase profits worth of Rp 5.25 million. According toÂ  BEP value the JS farmers will experience a loss if the decrease in yield is higher than 63% and the NJS farmers obtain lower tolerance with 56%. The results of sensitivity analysis with various scenarios showed that super jarwo farming still provides an adequate level of profit even though it tends to decrease.